Cybercrimes: A Proposed Taxonomy and Challenges - Harmandeep Singh Brar; Gulshan Kumar (Journal of Computer Networks and Communications)
Cybersecurity is one of the most important concepts of cyberworld which provides protection to the cyberspace from various types of cybercrimes. This paper provides an updated survey of cybersecurity. We conduct the survey of security of recent prominent researches and categorize the recent incidents in context to various fundamental principles of cybersecurity. We have proposed a new taxonomy of cybercrime which can cover all types of cyberattacks. We have analyzed various cyberattacks as per the updated cybercrime taxonomy to identify the challenges in the field of cybersecurity and highlight various research directions as future work in this field.